Three-dimensional magnetic resonance pelvimetry: A new technique for evaluating the female pelvis in pregnancy. Issue 102 (May 2018) - Liao, K.D.; Yu, Y.H.; Li, Y.G.; Chen, L.; Peng, C.; Liu, P.; Chen, C.L.; Chen, R.Y.; Zhong, M.; Wang, Y.
Highlights: Three-dimensional magnetic resonance pelvimetry in pregnant women is introduced. Pelvimetric reference values of Chinese females of childbearing age are established. Anterior-posterior diameters of the pelvis in Chinese females overall are smaller than the published datas. The previously described 3D computed tomography pelvimetry for predicting cephalopelvic disproportion show a limited predicted value in Chinese female population. Abstract: Objective: To describe three-dimensional (3D) magnetic resonance imaging (MRI) pelvimetry methods and to establish the pelvimetric reference in a large population of Chinese females at term pregnancy. Methods: Three-hundred one pregnant women at term who underwent MRI were included. Three-dimensional pelvic models were reconstructed using Mimics. 10.0 software based on MRI data sets, and measurements of these models were made. Pelvimetric results according to delivery modality were presented. Additionally, the previously described CT 3D pelvimetry method for predicting cephalopelvic disproportion (CPD) was used to validate its accuracy. Results: Two hundred ten women underwent vaginal delivery, and 13 underwent caesarean delivery for CPD. 3D modelling of the pelvis of pregnant women was feasible using MR data sets. Pelvimetric parameters in the vaginal delivery group were as follows: transverse diameter, 134.7 mm ± 7.5; obstetric conjugate, 126.9 mm ± 8.3; interspinous distance, 113.4 mm ± 8.2; sagittal midpelvis, 117.8 mm ± 8.1; intertuberous distance, 127.1 mm ± 10.4; sagittal outlet, 110.2 mm ± 8.9, and posterior sagittal outlet, 59.7 mm ± 8.1. According to the previously described CT 3D pelvimetry method for predicting CPD, 67.6% (142/210) of women in the vaginal delivery group were diagnosed with CPD. Conclusion: 3D MR pelvimetry is a novel method for determining pelvic dimensions at term pregnancy. A prospective trial is needed to establish a useful value for predicting CPD in Chinese females at high risk of CPD.